The Impact of Tumor Mutation Burden on the Effect of Frontline Trastuzumab Plus Chemotherapy in Human Epidermal Growth Factor Receptor 2-Positive Advanced Gastric Cancers - Kim, Hye Ryeon; Ahn, Soomin; Jo, Hyunji; Kim, Hongsik; Hong, Joohyun; Lee, Jeeyun; Lim, Ho-Yeong; Kang, Won Ki; Kim, Seung Tae (Frontiers in Oncology, 2021)
Background Trastuzumab is a HER2-trargeted humanized monoclonal antibody that has been studied as a first-line treatment for patients with HER2-positive advanced gastric cancer (AGC). The effect of anti-HER2 therapy according to tumor mutational burden (TMB) in HER2-positive AGC remains unclear. Methods We performed next-generation sequencing (NGS), including TMB analysis, in 31 HER2-positive AGC patients with trastuzumab plus chemotherapy as first-line therapy for recurrent (n=8) or metastatic (n=23) tumors. The TruSight Oncology 500 Assay from Illumina (San Diego, CA, USA) was used to evaluate TMB. Results Among 31 patients, 30 had tumors with immunohistochemistry (IHC) 3+, and one was IHC 2+ and silver in situ hybridization (SISH) positive. The median age was 57.0 years old (range, 35-76), and the majority had tumors with low TMB (87.1%, n=27/31). Only four (12.9%) had tumors with high TMB. Of these four, three achieved complete response (CR) or partial response (PR) to treatment, and the remaining patient was not evaluable for tumor response. Objective response rate (ORR) to trastuzumab plus chemotherapy showed a favorable trend in patients with high TMB (75.0%, n=3/4) compared to patients with low TMB (59.3%, n=16/27) (P=0.546). The median progression-free survival (PFS) was not reached in the TMB-high group but was 8.0 months (95% CI, 7.6-8.5) in the TMB-low group (P=0.019) Conclusion The status of TMB could be a novel biomarker in predicting the efficacy of trastuzumab plus chemotherapy in HER2-positive AGCs.